2015
DOI: 10.1007/s10899-015-9530-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of Prevalence and Risk Factors of Problem and Pathologic Gambling in North Cyprus

Abstract: In this article, the results of the national survey of adult gambling behavior in North Cyprus (NC) in 2012 are presented. The aim of this study is to investigate the characteristics of adults' participation in gambling, and to determine the prevalence of 'problem and pathological gambling' in NC. The population of this study was formed from all the people living permanently in NC, speaking Turkish, and within the age group 18-65. Household interviews were conducted with 966 people. To obtain data, a 30 item q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Ratios of NC (29) correspond to those found in Puerto Ricans in Puerto Rico (30), the Maoris in New Zealand (31) and Native Americans in North Dakota (32). The reasons of finding such similar ratios of Pg are explained by Volberg (30) as similar colonization, limited economy and sociological problems (29). In present study it is found out that the level of PPG is high among the university students.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Ratios of NC (29) correspond to those found in Puerto Ricans in Puerto Rico (30), the Maoris in New Zealand (31) and Native Americans in North Dakota (32). The reasons of finding such similar ratios of Pg are explained by Volberg (30) as similar colonization, limited economy and sociological problems (29). In present study it is found out that the level of PPG is high among the university students.…”
Section: Discussionsupporting
confidence: 71%
“…In the study, it is found that the PPG among university students are more prevalent rather than the general population. This claim is supported by a corresponding study (29) which found out that in NC at the age of 18 to 65 year group the pg ratio is 9.5% and Pg for life ratio is 3.5%. It is found that the trend of Pg is 2% in Asian countries like Hong Kong, Singapore and Macau (54,55).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations